75 Years of History on Concrete Floors - Karl Banghard (EXARC, 2012)
In 2011 the archaeological open-air museum Oerlinghausen (member of EXARC) turned 75 years old, and with that it is one of the oldest archaeological open-air museums in the world. It is, at least, oldest Germanic open-air museum.